Pengaruh Komunikasi dan Partisipasi Kader Lingkungan Terhadap Keberhasilan Program Kampung Iklim di Kota Surabaya - Adelia Safira; Deby Febriyan Eprilianto; Muhammad Farid Ma’ruf; Galih Wahyu Pradana (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
This study analyzes the influence of communication from the Surabaya City Environmental Agency (DLH) and the participation of environmental cadres on the success of the Climate Village Program (ProKlim) using a quantitative approach with a survey method on 110 environmental cadres selected through probability sampling techniques with a stratified sampling method. The results of multiple linear regression analysis show that DLH communication and environmental cadre participation partially and simultaneously have a positive and significant effect on the success of ProKlim, with a regression equation of Y = 3.455X1 + 0.608X2. The coefficient of determination value of 73% indicates that the success of the program is largely influenced by these two variables. This finding confirms that the synergy between effective government communication and active participation of environmental cadres is an important factor in supporting the success of the Climate Village Program in Surabaya City.